2008
DOI: 10.1111/j.1365-2826.2008.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue‐Specific Processing of Pro‐Opiomelanocortin

Abstract: In 1967, a new era in endocrinology was born. A set of pulse chase experiments performed by Steiner and Oyer (1) elegantly showed, for the first time, that insulin was derived from a larger precursor molecule, proinsulin. The radical revelation, that bioactive peptides are derived from larger precursors, forever changed endocrinology and, from then on, the concept of hormone precursors (or prohormones) has become a central dogma. Subsequently, the use of both traditional protein sequence studies and recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 73 publications
2
81
0
Order By: Relevance
“…As with the 'tissue-specific processing' of endogenous POMC suggested in rodents (Bicknell, 2008), the anterior domain of the pituitary gland is also the key compartment of POMC-expressing cells involved in the production of ACTH and functional regulation of zebrafish interrenal steroidogenesis . Our results have confirmed that the promoter selected for the regulation elements in this transgenic line contains the proper region for reporting endogenous anterior pituitary POMC mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with the 'tissue-specific processing' of endogenous POMC suggested in rodents (Bicknell, 2008), the anterior domain of the pituitary gland is also the key compartment of POMC-expressing cells involved in the production of ACTH and functional regulation of zebrafish interrenal steroidogenesis . Our results have confirmed that the promoter selected for the regulation elements in this transgenic line contains the proper region for reporting endogenous anterior pituitary POMC mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The POMC gene encodes a polypeptide precursor that undergoes extensive, "tissue-specific" posttranslational modification to generate a range of smaller and biologically active peptides, including adrenocorticotropin (ACTH) and α-, β-, γ-melanocyte-stimulating hormone. For instance, the processing of POMC in anterior pituitary corticotrophs results in the generation of pro-γ-MSH, ACTH, and β-LPH (Bicknell, 2008). These POMC-derived hormones regulate many physiological processes including steroidogenesis, skin pigmentation, food intake, and energy balance (Coll et al, 2004(Coll et al, , 2005Coll and Tung, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ACTH is mainly produced in the corticotropic cells from the anterior pituitary, but is also produced in the brain, adrenal medulla, skin, and placenta (Vrezas et al 2003, Bicknell 2008, Evans et al 2012. As ACTH is the most potent stimulus of the adrenal cortex, most of the knowledge on its mechanism of action derives from studies on the adrenal cortex or ACTH receptor-expressing cells.…”
Section: Introductionmentioning
confidence: 99%
“…The ACTH-related pituitary hormones are processing products of a common precursor protein named pro-opiomelanocortin (POMC). Enzymatic cleavage of this prohormone produces the following peptides: signal peptide, N-terminal glycopeptide, γ-melanocyte-stimulating hormone (γ-MSH), joining peptide, ACTH, α-melanocyte-stimulating hormone (α-MSH), corticotropinlike intermediate peptide (CLIP), β-lipotropin (β-LPH), γ-lipotropin (γ-LPH), and β-endorphin (16).…”
Section: Significancementioning
confidence: 99%